Tuning temperature coefficient of elastic modulus by heat treatment in a compositionally-modulated Ti-Nb-based alloy. (1st April 2023) - Gong, Delun; Wang, Haoliang; Wang, Qiushuang; Li, Shujun; Lin, Kun; Wang, Yandong; Yang, Rui; Hao, Yulin
Abstract: Temperature coefficient of elastic modulus can be positive for metastable β phase in titanium alloys whereas the precipitation of α phase from the β matrix phase results in a negative coefficient. This abrupt transition inspires us to tune the coefficient from positive, via zero of Elinvar effect, to negative by aging treatment in a Ti-Nb-based alloy. Here reports that its coefficients are continuously tunable by a compositionally-modulated β+α" dual-phase microstructure induced by spinodal decomposition. As the aging time increases at 723 K, the coefficient keeps positive almost unchanged initially, then drops quickly toward zero, and finally decreases slowly of being negative. A mixture rule modeling suggests that the coefficients of both phases decrease gradually from positive of being metastable to negative of being stable. These findings provide a new strategy to achieve Elinvar effect by optimizing the compositionally-modulated microstructure via heat treatments. Graphical abstract: Image, graphical abstract